KOMPETENSI APARATUR PEMERINTAH DAERAH DALAM ERA REFORMASI - Budiman Sakti (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2019)
The implementation of the district/city government constitution in Indonesia during the